Electrochemical cell
By using sodium ion conductive ceramic electrolyte and porous metal sheet in ZEBRA batteries, combined with the curved edge structure of carbon felt and ceramic electrolyte, the sealing problem caused by the change in the electrode assembly volume at high temperature is solved, and the lower temperature is achieved The stable operation and rapid start ensure continuous electrical connection of the battery stack.
Patent Information
- Application Number
- CN202380036898.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-27
- Filing Date
- 2023-04-25
- Publication Date
- 2024-12-13
AI Technical Summary
Existing ZEBRA batteries are sealed due to changes in the electrode assembly volume during high temperature operation, which affects the stability and continuity of the battery stack.
A rechargeable electrochemical cell is designed, using sodium ion conductive ceramic electrolyte elements and porous metal sheets, combined with carbon felt to support the ceramic sheets, and forming sodium metal through the anode surface of the ceramic electrolyte, using ceramic electrolyte The curved edges and pocket structure adjust the volume changes of the cathode chamber to ensure the sealing and electrical connection of the battery at high temperatures.
The battery operated at lower temperatures is realized, which reduces stress caused by ambient heating, shortens the start-up time, and improves the conduction efficiency of sodium ions through the combination of ceramic electrolyte and carbon felt, ensuring the stability of the battery stack and Continuous electrical connection.
Smart Images

Figure CN119137767A_ABST
Abstract
Description
[0001] The present invention relates to electrochemical cells having a solid ionically conductive electrolyte / separator, each cell having a metal casing.
[0002] Many different types of electrochemical cells are known that require elevated temperatures to operate. These include cells in which the electrolyte must be at an elevated temperature to provide adequate conductivity; and cells in which the electrodes must be at an elevated temperature so that the electrode assembly is liquid. One such type of battery is a molten sodium / metal halide rechargeable battery, such as a sodium / nickel chloride battery, which may be referred to as a ZEBRA battery (see, e.g., JL Sudworth, "The Sodium / Nickel Chloride (ZEBRA) Battery (J. Power Sources 100 (2001) 149-163). The sodium / nickel chloride battery incorporates a liquid sodium negative electrode separated from a positive electrode by a solid electrolyte that conducts sodium ions. The solid electrolyte may, for example, be composed of beta alumina. The positive electrode comprises nickel, nickel chloride, and sodium tetrachloroaluminate, which is liquid during use and acts as a secondary electrolyte to allow sodium ions to be transported from the nickel chloride to the solid electrolyte. The positive electrode also incorporates aluminum powder. Partial replacement of the nickel with other transition metals, such as iron, may result in additional discharge voltage levels. The battery is operated at a temperature generally below 350°C, but must be above the melting point of sodium tetrachloroaluminate of 157°C, and the operating temperature is generally between 270°C and 300°C. During discharge, the general reaction is as follows:
[0003] Cathode (positive electrode): NiCl 2 +2Na + +2e - → Ni+2NaCl
[0004] Anode (negative electrode): Na → Na + +e -
[0005] The overall result is that anhydrous nickel chloride (in the cathode) reacts with metallic sodium (in the anode) to produce sodium chloride and nickel metal; and a cell voltage of 2.58V at 300°C.
[0006] A modified type of ZEBRA battery, that is to say a molten sodium-nickel chloride rechargeable battery, is described in WO 2019 / 073260. It uses an electrolyte element comprising a porous sheet of a non-reactive metal and an impermeable layer of a sodium ion-conducting ceramic bonded to one face of the porous sheet. Therefore, in the electrolyte element, strength can be provided by the metal sheet, and this enables the electrolyte thickness to be significantly reduced compared to that required in conventional ZEBRA batteries. This results in the battery or battery pack being able to operate adequately at significantly lower temperatures, such as below 200°C. In addition, the significantly thinner ceramic layer also significantly reduces the stress caused by heating from the environment, so the startup time from the environment can be only a few minutes. Both of these are commercially advantageous benefits. The impermeable layer is bonded to the porous metal sheet, and the bond can be through a porous ceramic sublayer. Such a battery includes a metal housing, which may have a peripheral flange.
[0007] An alternative form of molten sodium / nickel chloride battery is described in WO 2022 / 123246 (application PCT / GB2021 / 053215) in which the electrolyte is also a planar ceramic sheet that conducts ions of an alkali metal, and a porous planar sheet of inert metal is closely adjacent to and substantially in contact with the ceramic sheet over the entire area of the ceramic sheet to provide support for the ceramic sheet. The ceramic sheet is formed separately from the porous planar sheet, rather than by deposition onto it.
[0008] To obtain greater power output, it is known to arrange multiple cells in a stack. However, there may be problems with such stacks, for example due to changes in the volume of the electrode assembly during operation.
[0009] According to the present invention, a rechargeable electrochemical cell is provided, the electrochemical cell comprising two electrode compartments, one being an anode compartment and the other being a cathode compartment, the electrode compartments being partially enclosed by metal plates defining the end faces of the cell, the two compartments being separated by an impermeable, ion-conducting electrolyte element, the cell being a molten sodium / metal chloride cell, the electrolyte element being a sodium ion-conducting ceramic; and the cathode compartment in its uncharged state comprising a cathode mixture comprising metal powder, sodium chloride and sodium aluminum chloride (sodium tetrachloroaluminate, NaAlCl 4 ), and wherein the end faces of the plates enclosing the cathode chamber have a slightly concave central area before operation, which is surrounded by a flat peripheral edge.
[0010] The metal powder in the cathode mixture may be nickel or iron.
[0011] Prior to operation, the battery was uncharged and at ambient temperature. To make the battery functional, the battery was heated to a temperature above NaAlCl 4 The melting point of the cathode mixture is heated, for example, to 180°C. Due to the temperature change and the phase change, the volume of the cathode mixture increases. This volume increase is accommodated by a change in the curvature of the central area of the end face, without any change in the overall thickness of the cell. Obviously, the metal plate defining the slightly concave end face must be flexible enough to change its shape in this way. The concave face can have a uniform curvature, or can have curved edges and a base of a substantially flat recess.
[0012] In the manufacture of the battery, the cathode mixture may first be preformed into a free-standing structure (referred to as a "blank"). For example, a powder mixture comprising nickel powder, sodium chloride and aluminum powder and preferably also comprising small proportions of other ingredients such as iron sulfide, sodium iodide and sodium fluoride may be introduced into a mold, compacted, and then heated with molten sodium aluminum chloride (NaAlCl 4 ) is infiltrated, preferably under vacuum. When cooled to room temperature, the resulting blank is strong enough to be handled and can be assembled with other battery components.
[0013] Thus, the cell is a modified ZEBRA cell such that the anode compartment of the cell contains sodium metal when charged.
[0014] The cell has a ceramic sheet as its electrolyte to separate the anode chamber from the cathode chamber. The cell may also include a porous metal sheet, preferably adjacent to the ceramic sheet in the anode chamber, to provide support for the ceramic sheet, the ceramic sheet being formed by deposition as a layer onto the porous metal sheet or, alternatively, formed separately from the porous planar sheet. The ceramic electrolyte sheet must be impermeable to gases or liquids, although it is a conductor of sodium ions that must pass between the anode and cathode chambers during operation.
[0015] The anode chamber may also include carbon felt, preferably highly porous, such as long carbon fibers, to aid the transfer of sodium metal away from or toward the ceramic sheet during charge and discharge of the battery. The carbon felt is highly porous and is preferably graphite; it may be a paper-like sheet with an initial thickness of about 1.5 mm and may, for example, have a carbon fiber density of less than 200 g / m 2 , for example 100g / m 2 Surface density.
[0016] A porous metal sheet or carbon felt is provided adjacent to the anode face of the ceramic electrolyte, these being electrically connected to the anode plate so that sodium metal can form at that face of the electrolyte during charging of the cell and so that sodium can ionize at that face during discharge. As an alternative, the surface of the ceramic electrolyte may be coated with an electronically conductive coating on the surface facing the anode compartment. Such a coating may be graphite, or a polyphosphate glass containing particles of an electronically conductive material. The polyphosphate glass is a sodium ion conductor. The particles may be carbon powder, tin powder and / or aluminum flakes or aluminum powder.
[0017] The metal plate enclosing the anode chamber may also define a slightly concave end face, when initially assembled and prior to operation, i.e. when the cell is uncharged and at ambient temperature, so that it does not bulge when the chamber is filled with molten sodium on charge. It is desirable to assemble the cell under vacuum rather than in an inert atmosphere, as this ensures that there is no gas to induce pressure in the anode chamber during operation.
[0018] The metal forming the metal sheet is "inert", meaning that it does not chemically react with components of the battery with which it comes into contact during use; for example, it may be a metal such as nickel, or a ferritic steel with aluminum (such as the type known as Fecralloy (TM), or a steel that forms an electronically conductive and adherent scale such as a CrMn oxide scale when heated in air. The sheet may have a thickness of not more than 3.0 mm, or not more than 1.0 mm, or not more than 0.5 mm, such as 0.1 mm or 0.2 mm. If it is close to the ceramic electrolyte, it must be porous, so it has a very large number of through holes. If it is separate from the ceramic electrolyte, it does not need to be porous; and it may be another type of steel, such as stainless steel.
[0019] The porous sheet may have a non-porous edge around its periphery; this edge may make it easier to seal the periphery of the porous plate to an adjacent component of the battery. The edge may have a width of no more than 15 mm, such as 10 mm or 5 mm or 3 mm. The porous sheet is preferably in the anode compartment where it will help molten sodium wick towards the surface of the ceramic sheet. The edge of the porous sheet may be welded to the lip of an adjacent battery component, such as a plate forming the anode compartment.
[0020] The metal plates partially enclosing the anode chamber and the cathode chamber are also inert metals, which means that they do not react with the contents of the respective chambers during use. They can be stainless steel, or the metals mentioned above as suitable for the porous sheets.
[0021] Such cells operate at elevated temperatures. Conventional sodium / nickel chloride cells, or ZEBRA cells, operate at 280°C or 300°C. The operating temperature depends in part on the nature of the electrolyte and its ionic conductivity; cells having a thin layer of ceramic as electrolyte may have lower operating temperatures, for example in the range of 175°C to 225°C. In any case, the seals between the cell components must remain tight at the elevated temperatures of operation. The seals may use high temperature polymers, such as PTFE, or inorganic materials that are electrical insulators, such as mica or vermiculite. The seal of the anode chamber may use a carbon-based gasket, or if the ceramic is deposited on the porous sheet, the anode plate may actually be welded to the periphery of the porous sheet. High temperature polymers are preferably not used to seal the anode chamber because they may interact with the molten sodium.
[0022] As a further option, the flat peripheral edge surrounding the central region of the plate enclosing the cathode chamber may define at least one protrusion or recess, and the end face of the plate enclosing the anode chamber defines at least one matching recess or protrusion, so that when a plurality of such cells are stacked together, the matching protrusions and recesses of the end faces of adjacent cells engage with each other to keep the cells aligned.
[0023] The interlocking or engaging protrusions and recesses, or sockets and recesses, also ensure good electrical connection between consecutive cells in the stack.Preferably, a protrusion and recess are provided at or adjacent each corner of a polygonal cell, such as a square cell.
[0024] The invention will now be further and more particularly described, by way of example only, and with reference to the accompanying drawings, in which:
[0025] Figure 1 shows a cross-sectional view through a battery of the present invention;
[0026] Figure 2 Shows Figure 1 a partially cutaway perspective view of a battery; and
[0027] Figure 3 Shows the Figure 1 A modified cross-sectional view of a battery showing only the anode compartment.
[0028] refer to Figure 1, which shows a battery 10 of the present invention. The battery 10 operates at an elevated temperature and includes disc-shaped metal electrode plates 11 and 12, each defining a flat peripheral edge, between which is an impermeable sodium ion conductive electrolyte sheet 13. The anode electrolyte plate 11 has a flat peripheral edge 18, which is slightly wider than the edge of the cathode electrode plate 12, and a short sleeve portion 19 extends upwardly from the peripheral edge 18 (as shown). The battery 10 is square in plan view. The electrode plates 11 and 12 together with the electrolyte sheet 13 define an anode chamber 14 on one side of the electrolyte sheet 13, and a cathode chamber 15 on the other side of the electrolyte sheet 13, which contains chemical substances that interact to generate electricity due to ion passages through the electrolyte sheet 13. Around their perimeters, the edges of the electrode plates 11 and 12 are sealed to the electrolyte sheet 13 by a heat-resistant, electrically insulating sealant 17. In this example, the cell assembly is held together by crimping the upstanding edges of the sleeve portion 19 around the edges of the electrolyte sheet 13 and electrode plate 12, all of which are separated by an insulating sealant 17; this sealing and crimping arrangement is represented schematically.
[0029] Battery 10 is a sodium / nickel chloride battery. Electrode plates 11 and 12 may be stainless steel. In its charged state, battery 10 will contain sodium metal in anode chamber 14 and nickel chloride in cathode chamber 15. However, the battery will typically be assembled in a fully discharged state, with cathode chamber 15 initially filled with a powder mixture comprising nickel powder, sodium chloride, and sodium aluminum chloride (sodium tetrachloroaluminate, NaAlCl 4 ) and preferably also contains small proportions of other ingredients such as iron sulfide, sodium iodide and sodium fluoride and aluminum powder.
[0030] In particular, for ease of assembly, a powder mixture containing nickel powder and sodium chloride but without sodium aluminum chloride is placed in a mold and compressed; the compressed powder mixture is then infiltrated with molten sodium aluminum chloride under vacuum and then cooled to form a bonded blank 25. This blank 25 is placed in the cathode chamber 15, occupying most of the space; a layer of carbon felt (not shown) may be placed above the blank 25, between the blank 25 and the cathode plate 12.
[0031] The impermeable sodium ion conductive electrolyte sheet 13 may be NaSICON. The porous metal sheet 24 is adjacent to the electrolyte sheet 13 but separated therefrom by a layer of carbon felt 82. The porous metal sheet 24 provides mechanical support for the electrolyte sheet 13. Along two opposing sides, the peripheral portions of the porous metal sheet 24 are bent to form springs 80, which contact the inner surface of the anode plate 11 in the assembled battery 10, so that those springs 80 elastically push the porous metal sheet 24 toward the electrolyte sheet 13. The carbon felt 82 is easily wetted by molten sodium, so it helps to wick the molten sodium toward or away from the face of the electrolyte sheet 13.
[0032] In order to operate the battery 10, it must first be heated to a temperature above 157°C, for example 200°C, at which the sodium aluminum chloride is molten and at which the impermeable ceramic electrolyte sheet 13 will adequately conduct the sodium ions. The molten sodium aluminum chloride enables the sodium ions to diffuse between the sodium chloride and the electrolyte sheet 13. Thus, the battery can be charged by applying a voltage from an external power source between the two electrode plates 11 and 12, so that the sodium ions pass through the electrolyte sheet 13 to contact the carbon felt 82 in the anode space 14, where they form sodium metal, while in the cathode space 15, the remaining chloride ions react with nickel to form nickel chloride. The battery 10 is easily reversible, so it can be charged and discharged many times.
[0033] The porous metal sheet 24 providing support for the electrolyte sheet 13 may be a metal such as nickel or a ferritic steel with aluminum (such as the type known as Fecralloy (TM)), or a steel that forms an electronically conductive and adherent scale such as a CrMn oxide scale when heated in air. Most of the sheet 24 is porous to create a very large number of through holes, but the peripheral portion forming the spring 80 need not be porous.
[0034] Plate 12 has a central circular region 22 which is depressed so that when the cell is initially assembled and prior to operation, that is, when the cell is uncharged and at ambient temperature, the central circular region 22 forms a slightly concave outer surface. Central region 22 is surrounded by a substantially flat edge 23. When cell 10 is heated to its operating temperature, the increase in the volume of material in cathode chamber 15 is accommodated by the concave surface of central region 22 becoming flatter. This does not change the thickness of cell 10.
[0035] Also refer to Figure 2, which shows a perspective view of a battery 10 with its edges partially cut away, the plate 12 also defines a protrusion or projection 30 near each corner of the battery 10; the plate 11 defines a recess 32 in a directly opposite position. The projections 30 and recesses 32 have complementary shapes. Therefore, when two or more batteries 10 are assembled into a stack, the projection 30 of each battery 10 cooperates with the recess 32 of an adjacent battery 10. Not only do the projections 30 and recesses 32 ensure that the batteries 10 remain properly aligned, but the areas of the plates 12 and 11 defining the projections 30 and recesses 32 are also sufficiently rigid to ensure good electrical connection between consecutive batteries in the stack despite changes in the temperature of the batteries 10 and changes in the charge state of the batteries 10.
[0036] For the sake of clarity, the carbon felt 82 and the porous metal sheet 24 are shown in FIG. Figure 2 Not shown.
[0037] As an alternative, instead of providing the electrolyte in the form of a discrete sheet of ceramic 13, the electrolyte may instead be in the form of one or more layers of ceramic deposited onto a porous metal sheet. The metal sheet may be substantially identical to the metal sheet 24, but without the curved spring 80, so that it is planar. Preferably, a porous and permeable ceramic layer will first be deposited and bonded to the metal sheet, and then an impermeable sodium ion conductive ceramic layer will be deposited and bonded to the porous layer, completely covering the porous layer. The ceramic layer will cover all the pores throughout the porous metal sheet, but the edges of the sheet will not be porous. The edges may be in electrical contact with the anode plate 11, for example they may rest on the peripheral edge 18, they may be welded to the peripheral edge 18 to provide a seal, or they may be sealed to the edge 18 by a conductive gasket. Electrical contact may also be provided by carbon felt within the anode chamber 14.
[0038] As explained in the following paragraphs, in some cases, one or both of the carbon felt 82 and the porous metal sheet 24 may be omitted.
[0039] As another alternative, the edges of the carbon felt 82 and ceramic electrolyte sheet 13 may rest directly on the peripheral edge 18 of the anode plate 11. In this case, the porous metal sheet 24 may be omitted; the central portion of the anode plate 11 may be depressed to form a concave outer face similar to the region 22 of the cathode plate 12. At initial assembly in the cell, no sodium is present in the anode chamber 14. During charging, molten sodium forms at the anode face of the electrolyte sheet 13 and moves throughout the anode chamber 14 through the carbon felt 82 by capillary action.
[0040] Reference now Figure 3, which shows only the anode chamber 14a of a cell 10a which is an alternative modification to the cell 10; those components which differ from those of the cell 10 are indicated by the same reference numerals followed by 'a'. In this cell 10a, the anode face of the ceramic electrolyte sheet 13 is pre-treated, for example with a graphite coating, prior to assembly so that it is electronically conductive. The edges of the electrolyte sheet 13 are sealed to the peripheral edge 18 of the anode plate 11a by conductive gaskets 27, which may be carbon-based. The carbon felt 82 may therefore be omitted; and the porous metal sheet 24 is also omitted. The anode plate 11a defines a recess 32 adjacent each corner, but the central portion of the plate 11a is concave, which defines a curved edge 34 and a flat depressed area 36, which is shown in its initial form when the cell 10a is assembled; in this state, there is a narrow gap between the electrolyte sheet 13 and the flat depressed area 36 of the plate 11a. During charging of the cell 10a, sodium is formed at the anode face of the electrolyte sheet 13. Capillary action in the narrow gap between the face of the electrolyte sheet 13 and the depressed area 36 of the anode plate 11a distributes the molten sodium throughout the chamber 14a. As shown by the dashed line 38, as the sodium fills the chamber 14a, the depressed area 36 moves away from the electrolyte sheet 13, increasing the available volume in the chamber 14a.
[0041] Instead of coating the surface of the ceramic electrolyte sheet 13 with graphite, other materials can be used for this purpose. For example, the anode surface of the ceramic electrolyte sheet 13 can be painted with an aqueous solution of sodium polyphosphate containing carbon powder, tin powder and / or aluminum flakes or aluminum powder, and then dried and fired. Sodium polyphosphate forms a sodium ion conductive glass, and the metal or carbon particles allow electronic conduction. Other options are to coat or paint the surface with lead acetate in an aqueous solution or tin (II) chloride in a solution in ethanol, and then dry and fire the surface; fire in an oxygen-free atmosphere to produce a mixture of Pb (IV) oxide and Pb metal, or a mixture of Sn (IV) oxide / chloride and Sn metal, all of which are conductive. The resulting metal and small particles of metal oxide or metal chloride on the surface allow conduction.
[0042] It will be appreciated that the battery 10 may be modified by using a cathode plate 12 having a Figure 3 The anode plate 11a shown in FIG. 1 is similarly concave in shape, defining curved edges and depressed portions similar to edge 34 and depressed portion 36. In a cell having this modification, the depressed portion may be pressed directly against the surface of blank 25 during initial assembly.
Claims
1. A rechargeable electrochemical cell comprising two electrode chambers, one being an anode chamber and the other being a cathode chamber, the electrode chambers being partially enclosed by metal plates defining the end faces of the cell, the two chambers being separated by an impermeable, ion-conducting electrolyte element, the cell being a molten sodium / metal chloride cell, the electrolyte element being a sodium ion-conducting ceramic; and the cathode chamber in its uncharged state containing a cathode mixture comprising metal powder, sodium chloride and sodium aluminum chloride (sodium tetrachloroaluminate, NaAlCl4), and wherein the end faces of the plates enclosing the cathode chamber have, prior to operation of the cell, a slightly concave central region surrounded by a flat peripheral edge.
2. A battery as described in claim 1, wherein the flat peripheral edge surrounding the central area of the plate enclosing the cathode chamber defines at least one protrusion or recess, and the end face of the plate enclosing the anode chamber defines at least one matching recess or protrusion, so that when a plurality of such batteries are stacked together, the matching protrusions and recesses of the end faces of adjacent batteries engage with each other to keep the batteries aligned.
3. A battery as claimed in claim 2, having substantially square end faces, wherein a protrusion and a recess are provided at each corner of the square battery.
4. A battery as claimed in any one of the preceding claims, wherein the metal powder in the cathode mix is nickel or iron.
5. A battery as claimed in any preceding claim, wherein the battery further comprises a porous metal sheet arranged to provide support to the impermeable electrolyte element.
6. A battery as claimed in claim 5, wherein the impermeable electrolyte element is separated from the porous metal sheet by a layer of carbon felt.
7. The battery of any one of claims 1 to 4, wherein the electrolyte element is coated with an electronically conductive coating on the surface facing the anode compartment.
8. A battery as claimed in claim 7, wherein the coating is a polyphosphate glass containing particles of electronically conductive material.
9. A battery as claimed in claim 8, wherein the particles are carbon powder, tin powder and / or aluminium flakes or aluminium powder.
10. A battery as claimed in any one of the preceding claims, wherein the metal plates partially enclosing the anode chamber and the cathode chamber are metals which do not react with the contents of the respective chambers during use, the metal being stainless steel, or nickel, or ferritic steel with aluminium, or steel which forms an electronically conductive and adherent scale, such as a CrMn oxide scale, when heated in air.
